Profits in economic theory - Howard Michael (London, 1983)
Discontent with the prevailing economic orthodoxy grew as the long period of economic expansion in the advanced capitalist economies came to an end in the 1970s. Many economists looked for a more fruitful point of departure in the ideas of Marx and the classical economists and also in such contemporary economists as Kalecki and Sraffa. Radical Economics takes up the challenge to try to interpret the world better than current conventional economics. Each book in the series is a substantive contribution in its field and should become a text around which the study of economics will take place.
Keywords: Economic theory